Prevent Osteoporosis: Catch the Silent Thief - Linda B. Bobroff (EDIS)
About 50 percent of women and 25 percent of men over age 50 will have a bone fracture caused by osteoporosis in their lifetimes. Many of these fractures, especially in the spine and hip, cause pain, disability, and loss of independence. About 24 percent of people aged 50 and over who have a hip fracture die in the year following the fracture. Learn more in this revised 8-page fact sheet written by Linda B. Bobroff and published by the UF Department of Family, Youth and Community Sciences, March 2012.